Regular endoscopic surveillance and polypectomy is effective in managing rectal adenoma progression following colectomy and ileorectal anastomosis in patients with familial adenomatous polyposis. (25th November 2021) - Anele, Chukwuemeka C.; Xiang, Jinpo; Martin, Isabel; Hawkins, Menna; Man, Ripple; Clark, Susan K.; Faiz, Omar D.; Latchford, Andrew
Abstract: Aim: Total colectomy with ileorectal anastomosis (TC‐IRA) is a surgical option for patients with familial adenomatous polyposis (FAP). Regular endoscopic surveillance of the rectum is recommended to prevent rectal cancer. We aimed to document polyp progression in the rectum following TC‐IRA and evaluate the role of polypectomy during surveillance. Method: Patients with FAP who underwent TC‐IRA between 1990 and 2017 were identified. Demographic, endoscopic and genetic data were retrieved. Cumulative rectal adenoma (polyp) counts were obtained, whilst accounting for any polypectomies during the study period. The rate of polyp progression and factors influencing secondary proctectomy were evaluated. Results: One hundred and ninety‐nine patients fulfilled our inclusion criteria, of which 44% were male. The median age at colectomy was 19 (range 11–70) years and median preoperative rectal polyp count was 7 (range 0–50). All patients had an APC pathogenic variant, of which 151 (79%) were 5' of the mutation cluster region (MCR), 19 (10%) in the MCR, six (3%) were 3' of the MCR and 15 (8%) had a gross deletion. After a median follow‐up of 8.6 (range1–27) years and a median of 11 (range 2–37) flexible sigmoidoscopies per patient, the median rate of polyp progression was 5.5 polyps/year (range 0–70.2). There was no evidence of polyp regression. Eight (4%) patients underwent secondary proctectomy for neoplasia, of which one (0.5%) had rectal adenocarcinoma. A total of 13, 527 polyps were removed, a median of 35 polyps/patient (range 0–829). The rate of polyp progression was not significantly associated with genotypic or phenotypic factors. Conclusion: Progression of rectal adenoma burden following TC‐IRA appears to be slow and dependent on the length of follow‐up. In the modern era of stringent endoscopic surveillance and therapeutic procedures such as cold snare polypectomy, the rate of secondary proctectomy and the risk of rectal cancer after TC‐IRA are very low. These findings are important when counselling patients with regard to the choice of surgery for FAP and implementing endoscopic surveillance.